2019
DOI: 10.3390/hydrology6030066
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Desertification in Iran

Abstract: Iran has different climatic and geographical zones (mountainous and desert areas), mostly arid and semi-arid, which are suffering from land degradation. Desertification as a land degradation process in Iran is created by natural and anthropogenic driving forces. Meteorological drought is a major natural driving force of desertification and occurs due to the extended periods of low precipitation. Scarcity of water, as well as the excessive use of water resources, mainly for agriculture, creates negative water b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Roodposhti et al [27], using support vector machine algorithm, enhanced vegetation index (EVI), and SPI showed that in the duration of 1978-2008, the most severe drought was in 2008 in the study area, which is consistent with the results presented in Figure 8. Bazrafshan [28] and Emadodin et al [29] showed that, in recent years, at most stations in Iran, including stations in the Kermanshah, the severity of the drought has become more severe with time, which is consistent with the results of this study.…”
Section: Annual Time Seriessupporting
confidence: 91%
“…Roodposhti et al [27], using support vector machine algorithm, enhanced vegetation index (EVI), and SPI showed that in the duration of 1978-2008, the most severe drought was in 2008 in the study area, which is consistent with the results presented in Figure 8. Bazrafshan [28] and Emadodin et al [29] showed that, in recent years, at most stations in Iran, including stations in the Kermanshah, the severity of the drought has become more severe with time, which is consistent with the results of this study.…”
Section: Annual Time Seriessupporting
confidence: 91%
“…Changes in precipitation and seasonal water regimes can result in increased drought, thereby greatly affecting productivity [3]. Anthropogenic climate change, attributed to the greatly increased greenhouse gas (GHG) emissions since the 19th century, has been identified as a cause of increased frequency and severity of droughts [4,5]. Drought is a major contributing factor to land degradation [6], a process that is further accelerated by unsustainable land-use practices such as overgrazing and urbanization [7][8][9][10][11][12], and it has serious potential consequences for global food security.…”
Section: Introductionmentioning
confidence: 99%
“…The overuse of soil as a consequence of inappropriate management to meet increasing food demand, including intensive use of fertilizers and pesticides and monoculture cropping, has had direct and adverse effects on soil ecosystem functions and services. Therefore, population growth and soil degradation are often closely linked (Emadodin and Bork 2012;Emadodin et al 2019). Moreover, the conversion of woodland and rangeland into agricultural land for crop and biofuel production has accelerated and triggered additional environmental loads (Millennium Ecosystem Assessment 2005;Emadodin et al 2009;Lobell et al 2011;Bedunah and Angerer 2012;Taube et al 2014;Lal 2015;Vimal et al 2017).…”
Section: Introductionmentioning
confidence: 99%